A simulation study of random caps on a sphere. (24th August 2016) - Solomon, H.; Sutton, C.
Abstract : This paper describes the computer simulation of a coverage problem in geometric probability, that of placing random caps on the surface of a sphere. The simulation results were compared with exact values, where known, and the differences were negligible. This suggested the use of simulation results to assess several approximation formulas in the literature.